ANALISIS KESALAHAN BERBAHASA PADA TEKS EKSPLANASI KOMPLEKS KARYA SISWA SEKOLAH MENENGAH ATAS - Saputra, Noviardi Ari; Sumarwati, Sumarwati; Rohmadi, Muhammad (Universitas Sebelas Maret, 2020)
The purpose of this study are to describe and explain: (1) the variety of language errors in complex explanation text of the student work of XI MIPA 1 SMA Negeri 7 Surakarta, (2) the most dominant language errors, (3) causes of error, and (4) teacher's effort to overcome the causes of language error in writing complex explanatory text of students. The results of this study are as follows. First, there are four elements of language errors in complex explanation text of the student work, namely: spelling, diction, sentence, and paragraph. Second, the dominant language errors in the complex explanatory text of the student work are a spelling mistake. Thirdly, language errors that often occur in the complex explanatory text of the student work is caused by several factors, as follows: lack of learning time about spelling due to integrated with existing Indonesian language materials, less thorough in writing, low motivation of students in writing because writing is difficult, as well as student habits of writing without regard to EYD. Fourth, efforts can be made to overcome the causes of language errors in writing complex explanatory texts, among others: increase the spelling time of spelling, increase writing exercises, foster student motivation in writing activities, and increase student mastery of spelling and language rules.